Slit-beam retro-illumination assisted phacoemulsification for cataract with coexisting corneal opacity - Kusumesh, Rakhi; Sinha, Bibhuti Prassan; Ambastha, Anita; Bhasker, Gyan; Mohan, Nilesh (Nepalese Journal of Ophthalmology, 2020)
Introduction: We describe a novel surgical technique of slit-beam retro-illumination assisted phacoemulsification for cataract with coexisting corneal opacity. Cases: We present two cases with cataract and coexisting opacity, who underwent slitbeam retro-illumination assisted phacoemulsification and further application of same process in 12 patients. Conclusion: This technique is safe and provides excellent visualization during cataract surgery in patients with corneal opacities.